2012
DOI: 10.1530/jme-12-0099
|View full text |Cite
|
Sign up to set email alerts
|

Essential roles of 11β-HSD1 in regulating brown adipocyte function

Abstract: Brown adipose tissue (BAT) increases energy expenditure and is an attractive therapeutic target for obesity. 11b-Hydroxysteroid dehydrogenase type 1 (11b-HSD1), an amplifier of local glucocorticoid activity, has been shown to modulate white adipose tissue (WAT) metabolism and function. In this study, we investigated the roles of 11b-HSD1 in regulating BAT function. We observed a significant increase in the expression of BAT-specific genes, including UCP1, Cidea, Cox7a1, and Cox8b, in BVT.2733 (a selective inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
(35 reference statements)
4
26
0
Order By: Relevance
“…Consistent with these findings, gene expression of MR was upregulated in WAT of obese mice (56). It has been reported that 11␤-HSD1 inhibition decreased WAT mass, adipocyte hypertrophy, and adipose tissue fibrosis (113), whereas it increased the expression of BAT-specific genes (including UCP1) in obese rats (73).…”
Section: Adipose Tissue Local Factors: Potential Implications Of the supporting
confidence: 79%
“…Consistent with these findings, gene expression of MR was upregulated in WAT of obese mice (56). It has been reported that 11␤-HSD1 inhibition decreased WAT mass, adipocyte hypertrophy, and adipose tissue fibrosis (113), whereas it increased the expression of BAT-specific genes (including UCP1) in obese rats (73).…”
Section: Adipose Tissue Local Factors: Potential Implications Of the supporting
confidence: 79%
“…Dexamethasone significantly reduced the isoprenaline-induced OCR of brown adipocytes, the major component of which was uncoupled oxidation. These observations on human brown adipocytes are supported by results from studies on rodents (Soumano et al 2000, Rodríguez & Palou 2004, Liu et al 2013. The stimulation, by exposure to cold or isoprenaline, of expression of UCP1 of BAT from the intrascapular region is inhibited by GCs (Soumano et al 2000).…”
Section: Figuresupporting
confidence: 53%
“…Consistent with these findings, the MR mRNA expression levels were significantly upregulated in the WAT of the obese mice [102]. Third, the 11β-HSD1 inhibition decreased the WAT mass, adipocyte hypertrophy, and adipose tissue fibrosis [103,104], whereas it increased the expression of the BAT-specific genes (including UCP1) in the obese rats [105]. Four, we confirmed the presence of the MR mRNA in the WAT of the adult rats.…”
Section: Actions Of Glucocorticoids In Adipose Tissue Activitysupporting
confidence: 78%